IL-17A injury to retinal ganglion cells is mediated by retinal Müller cells in diabetic retinopathy - Ao-Wang Qiu (Nature Publishing Group, 2021)
Abstract Diabetic retinopathy (DR), the most common and serious ocular complication, recently has been perceived as a neurovascular inflammatory disease. However, role of adaptive immune inflammation driven by T lymphocytes in DR is not yet well elucidated. Therefore, this study aimed to clarify the role of interleukin (IL)-17A, a proinflammatory cytokine mainly produced by T lymphocytes, in retinal pathophysiology particularly in retinal neuronal death during DR process. Ins2Akita (Akita) diabetic mice 12 weeks after the onset of diabetes were used as a DR model. IL-17A-deficient diabetic mice were obtained by hybridization of IL-17A-knockout (IL-17A-KO) mouse with Akita mouse. Primarily cultured retinal Müller cells (RMCs) and retinal ganglion cells (RGCs) were treated with IL-17A in high-glucose (HG) condition. A transwell coculture of RGCs and RMCs whose IL-17 receptor A (IL-17RA) gene had been silenced with IL-17RA-shRNA was exposed to IL-17A in HG condition and the cocultured RGCs were assessed on their survival. Diabetic mice manifested increased retinal microvascular lesions, RMC activation and dysfunction, as well as RGC apoptosis. IL-17A-KO diabetic mice showed reduced retinal microvascular impairments, RMC abnormalities, and RGC apoptosis compared with diabetic mice. RMCs expressed IL-17RA. IL-17A exacerbated HG-induced RMC activation and dysfunction in vitro and silencing IL-17RA gene in RMCs abolished the IL-17A deleterious effects. In contrast, RGCs did not express IL-17RA and IL-17A did not further alter HG-induced RGC death. Notably, IL-17A aggravated HG-induced RGC death in the presence of intact RMCs but not in the presence of RMCs in which IL-17RA gene had been knocked down. These findings establish that IL-17A is actively involved in DR pathophysiology and particularly by RMC mediation it promotes RGC death. Collectively, we propose that antagonizing IL-17RA on RMCs may prevent retinal neuronal death and thereby slow down DR progression.